Mentha arvensis LINN) (An Experiment on the Distillation and Physico-chemical Determination of Mentha (Mentha) - Gasik Darma (Balai Besar Industri Agro, 1986)
Experiments on the distillation and characterization of mentha leaves essential oil have been done using three type of leaves, e.g. Mentha arvensis var.piperascence ex Sukabumi and Bogor, and Mentha arvensis var. javanica ex Bogor. The yield of oil were 2.0%;1.8% and 2.7%, respectively. Menthol content of the oil were 67.6% (mentha arvensis var. piperascence ex Sukabumi) and 53.6% (M.arvensis var. piperascence ex Bogor). No menthol can be detected in the oil of M.arvensis var. javanica.